A Life-Threatening Neurotoxicity in Bungarus Candidus Snake Bite: A Case Report - Zaki Rusmana Putra; Togar Anthoni; Chris Eko Budiharto (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2024)
Background: Bungarus Candidus is a snake that induces severe neurotoxic symptoms. Case: A 31-year-old female came to the emergency department with complaints of pain in the whole body, limb weakness, shortness of breath, and epigastric pain after being bitten by a snake. Neurological examination, ptosis of both eyelids was found with normal movement of the eyeballs. Muscle strength in all extremities is 4, followed by decreased physiological reflexes. There are fang marks in the form of 2 slightly swollen and reddened black dots on the left foot. During observation, the patient had decreased consciousness and severe shortness of breath with desaturation without any signs of shock. Other clinical revealed bilateral dilated pupils, dysphonia, dysarthria, and muscle strength that was difficult to assess. The patient was intubated and subsequently admitted to the ICU. The patient regained consciousness but still had difficulty opening his eyes and weak muscle strength on the 2nd of ICU. The patient's condition improved on the 5th of ICU, extubating was performed and transferred to the non-ICU. The treatment obtained included 17 vials of SABU, analgesics, antibiotics, anticholinesterase, and anticholinergic. The patient was discharged after 11 days of hospitalization. Discussion: The neurotoxicity of snake venom is related to mechanisms of neuromuscular transmission blockade, pre-synaptic and post-synaptic. Bungarus Candidus has a peculiar type of toxin, candoxin, that inhibits nicotinic acetylcholine receptors at the postsynaptic site. Conclusion: Prompt recognition of symptoms and management interventions in snakebite cases are critical to patient outcomes and survival.